(untitled) (Colombia Medica, 1989)
Intra-abdominal sepsis presents a 30-80% mortality rate when the traditional management of laparotomy and septic site drainage is implemented. This article discusses various methods for preventing re-occurring abdominal sepsis. It describes techniques used and results achieved using an open abdomen in the management of intra-abdominal sepsis in the Valle University Hospital, Cali, Colombia. This study spans 18 months and involves 65 patients, all of whom presented abdominal sepsis. Initial patients were treated with plastic mesh insertion, and the remaining patients received nylon mesh with a zipper. Techniques described include mesh insertion and protocol for daily abdominal lavage. The patients in this study were classified according to the degree of sepsis hemodynamic status based on the APACHE II scale and PATI. The primary indication for mesh insertion was generalized suppurative peritonitis. An average of 4.74 lavages were performed on surviving patients, and the mesh was left in place for 11.5 days. The mortality rate for these patients was 31.5%.